Framing Produser pada Proses Produksi Program Pentas Ceria Lembaga Penyiaran Publik Lokal (LPPL) TV Peduli Kota Parepare - Muliani, Rina Yustika (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
This thesis discusses the framing by producers in the production process of a TV program. The first problem statement is about how the production process of the "Pentas Ceria" program by LPPL TV Peduli is conducted. The second problem statement focuses on how the producers frame the "Pentas Ceria" program by LPPL TV Peduli. The research aims to understand the production process of the "Pentas Ceria" program by LPPL TV Peduli and to determine the framing by producers in the program. The research methodology used is qualitative. The data sources include the crew of LPPL TV Peduli in Parepare for the "Pentas Ceria" program (primary data) and documents, books, and journals (secondary data). The research instruments are the researchers themselves, and the data collection techniques include in-depth interviews, observations, and documentation of interview guides and document study guides. The study also employs framing theory and agenda-setting theory. The research results indicate that the production process involves three stages in creating the "Pentas Ceria" program by TV Peduli in Parepare. These stages are pre-production, which includes agenda and idea generation; production, which involves shooting and editing; and post-production, which includes airing, streaming, and program evaluation. Furthermore, the producers' framing utilizes various types of framing, including Robert Entman's framing schema, which employs forms and schemas that can make a program more complex.